Microplastic Threats: Urban–Rural Differences in Knowledge, Risk, and Psychosocial Factors among Households - Megawati Simanjuntak; Irni Rahmayani Johan; Ismayanti Pratiwi; Nurazizah Aprilia; Rohimatul Janah; Farhah Azizah Salsabila (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Microplastic pollution has emerged as an increasingly urgent environmental problem, highlighting the need to better understand the psychological and social factors that encourage households to engage in pro-environmental behavior. Grounded in the Theory of Planned Behavior, this study examines how microplastic knowledge, risk perception, attitudes, subjective norms, and perceived behavioral control shape pro-environmental intentions among urban and rural housewives, extending TPB by integrating knowledge and risk perception. Methods: A quantitative research design was applied by distributing structured questionnaires to 600 respondents, comprising 300 urban and 300 rural housewives in Bogor City and Bogor Regency. Data analysis involved independent t-tests to identify differences between the two groups, and Structural Equation Modeling (SEM) to examine the causal relationships among the studied variables. Results: The results show significant urban–rural differences in microplastic knowledge, risk perception, subjective norms, and perceived behavioral control, while attitudes and pro-environmental behavioral intentions are relatively similar across contexts. In urban areas, knowledge significantly influences risk perception, whereas attitudes, subjective norms, and perceived behavioral control predict pro-environmental behavioral intention. In rural areas, risk perception and perceived behavioral control are the main predictors, with no direct effect of knowledge. Conclusion: Overall, knowledge alone is insufficient to promote pro-environmental behavioral intention. Instead, behavioral intentions follow context-specific pathways, driven primarily by attitudinal and normative factors in urban areas and by risk awareness and perceived behavioral control in rural settings.